Perancangan Brand Identity UMKM Cerys Bites di Kota Malang dengan Metode Moser untuk Membangun Brand Awareness - Santoso, Elsa Febritha; Nirwana, Aditya; Prasetya, Bintang Pramudya Putra (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2023)
Micro, Small, and Medium Enterprise play an important role in the Indonesian economy due its ability to evenly absorb the workforce, especially in the food and beverage sector, particularly in the snack industry like cookies, wafer, and biscuits. This development also evident in Malang City, which is home to numerous cookies brand and one of which is Cerys Bites. Despite its potential, Cerys Bites still lacks awareness compared to its competitors. To address this, a brand identity for Cerys Bites was designed to increase public awareness. The brand identity was developed using the Moser brand model and qualitative research method. Based on the analysis and synthesis of concepts, Cerys Bites was found to possess a core brand value, message, and personality that formed the visual concepts in its brand identity design. The results showed an increase in Cerys’s Bites Instagram account, as evidenced by higher activities such as like, comments, shares, and saves. The effectiveness test revealed a rise in Instagram engagement for Cerys Bites, demonstrating that a well-designed and consistent brand identity can successfully build public awareness.